Maximal Heights of Nearshore Storm Waves and Resultant Onshore Flow Velocities - Bujan, Nans; Cox, Rónadh (Frontiers in Marine Science, 2020)
Storm waves, after breaking or overtopping, generate strong onshore flows that do significant mechanical work, including eroding and transporting large boulders. The waves can be amplified on approach, and the flows themselves may be further intensified by local topographic effects. These processes are currently poorly parameterised, but are of great importance for understanding the interactions between waves and coasts. We present a highly generalised equation for estimating maximal coastal wave heights and consequent onshore flow velocities. Although very approximate, this method contains no embedded assumptions, and thus provides a more realistic first-order check of storm wave capabilities than previous approaches. Initial analysis suggests that amplified waves may generate maximal onshore flow velocities up to six times the phase speed of the offshore waves. Although the probability of occurrence in any given storm is very low, the possibility of such extreme values cannot be ignored, especially when interpreting ancient deposits of large boulders. The equations presented here can be used as a first-order test for coastal boulder deposits currently interpreted as tsunami deposits, to evaluate whether a storm-wave origin should be reconsidered. This approach could also be employed at coasts in general, to evaluate long-term probabilities of damaging flows, as a component of coastal risk analysis.